2011
DOI: 10.4274/npa.y5951
|View full text |Cite
|
Sign up to set email alerts
|

Ekstremite ve Gövde Distonileri; Botulinum Toksini Uygulamaları

Abstract: ÖZETEkstremite distonisi (ED) izole fokal bir semptom veya jeneralize distoninin bir parças› olabilir, maluliyet yarat›c› bir durumdur. ‹diopatik veya özellikle kontrlateral bazal ganglionlar› etkileyen durumlarda di¤er bir hastal›¤a sekonder olabilir. Yayg›n veya ciddi ED genellikle oral ilaçlar ile tedavi edilir. Stereotaksik cerrahi düflünülebilir. ‹diopatik ED veya fokal ekstremite semptomlar› ise botulinum toksini (BoNT) enjeksiyonuna iyi yan›t verir. BoNT tip A enjeksiyonlar› ED'li hastalar›n %80'inin üz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It has been reported that the maximum effect is observed 2-4 weeks after the injection and in subsequent weeks the effect decreases and symptoms return. As the effect is reduced after a mean of 3 months, it has been emphasised that it is necessary to repeat the injections on average every 3-4 months [18]. In this report, the case was presented of a patient with tardive dystonia who benefitted from physical therapy applications together with olanzapine and risperidone treatment for focal hand dystonia which developed associated with the use of antipsychotic medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the maximum effect is observed 2-4 weeks after the injection and in subsequent weeks the effect decreases and symptoms return. As the effect is reduced after a mean of 3 months, it has been emphasised that it is necessary to repeat the injections on average every 3-4 months [18]. In this report, the case was presented of a patient with tardive dystonia who benefitted from physical therapy applications together with olanzapine and risperidone treatment for focal hand dystonia which developed associated with the use of antipsychotic medication.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of extremity dystonia, the main objective is functional improvement and correction of abnormal posture. Opening a dystonic hand provides patient comfort and hand hygiene [18].…”
Section: Discussionmentioning
confidence: 99%